The Relationship Between Spiritual Well-Being, Resilience, and Adherence Among Patients Receiving Hemodialysis Treatment in Türkiye - Bulbul, Elif; Sukut, Ozge; Dikec, Gul (Springer, 2026)
This study examined the relationship between spiritual well-being, resilience, and adherence of hemodialysis patients and the factors affecting them. The data were collected from 182 hemodialysis patients receiving treatment in a dialysis center who met the inclusion criteria by purposive sampling method in Istanbul. The data were collected with the patient description questionnaire, which measures patient sociodemographic characteristics and characteristics related to the medical diagnosis, the Spiritual Well-Being Scale, the Brief Resilience Scale, and the End-Stage Renal Failure-Adherence Questionnaire. Gender, educational status, employment status, and mean age of patients were found to be correlated with psychological resilience. Marital status, employment status, cohabitants, and mean age of patients were found to be correlated with spiritual well-being. Gender, number of weekly dialysis sessions, and dialysis competencies were found to be correlated with hemodialysis patients' adherence to their treatment. Hemodialysis patients' adherence was positively correlated with both the faith subscale of spiritual well-being and psychological resilience. According to regression analysis, gender and resilience explained 12.8% of the total variance of adherence. This study determined that resilience is an essential factor in increasing the adherence of hemodialysis patients.
Keywords: Adherence; Hemodialysis; Resilience; Spirituality; Spiritual Well-Being